A Randomized Trial of Off‐Site Collaborative Care for Depression in Chronic Hepatitis C Virus. (11th September 2017) - Kanwal, Fasiha; Pyne, Jeffrey M.; Tavakoli‐Tabasi, Shahriar; Nicholson, Susan; Dieckgraefe, Brian; Storay, Erma; Goetz, Matthew Bidwell; Kramer, Jennifer R.; Smith, Donna; Sansgiry, Shubhada; Tansel, Aylin; Gifford, Allen L.; et al.
Abstract : Objective: To test the effectiveness of a collaborative depression care model in improving depression and hepatitis C virus (HCV) care. Data Sources/Study Setting: Hepatitis C virus clinic patients who screened positive for depression at four Veterans Affairs Hospitals. Study Design: We compared off‐site depression collaborative care (delivered by depression care manager, pharmacist, and psychiatrist) with usual care in a randomized trial. Primary depression outcomes were treatment response (≥50 percent decrease in 20‐item Hopkins Symptoms Checklist [SCL‐20] score), remission (mean SCL‐20 score, <0.5), and depression‐free days (DFDs). Primary HCV outcome was receipt of HCV treatment. Data Collection: Patient data were collected by self‐report telephone surveys at baseline and 12 months, and from electronic medical records. Principal Findings: Baseline screening identified 292 HCV‐infected patients with depression, and 242 patients completed 12‐month follow‐up (82.9 percent). Intervention participants were more likely to report depression treatment response, remission, and more DFDs than usual care participants. Intervention participants were more likely to receive antiviral treatment; however, the difference was not statistically significant. Conclusion: Off‐site depression collaborative care improved depression outcomes in HCV patients and may serve as a model for collaboration between mental health and specialty physical health providers in other high co‐occurring conditions.